Study guides

☆☆

Q: -6y plus 5 equals -67

Write your answer...

Submit

Still have questions?

Continue Learning about Calculus

-6y+3 = -7y+8 -6y+7y = 8-3 y = 5

-5x + 6y = 24 6y = 5x + 24 y = 5/6 x + 4 the slope is 5 6

2x + 6y = 93x - 12y = 15Chose the second equation because you can simplify it.3x - 12y = 15 divide by 3 to both sidesx - 4y = 5 add 4y to both sidesx = 4y + 5Replace 4y + 5 for x to the first equation.2x + 6y = 92(4y + 5) + 6y = 98y + 10 + 6y = 914y = -1y = -1/14x = 4y + 5x = 4(-1/14) + 5x = -2/7 + 5x = -2/7 + 35/7x = 33/7

(8 + 4) x 5...

-4

Related questions

6y+5 = 11y+30 -25 = 5y -5 = y

6y + (2-2)y = 6y 6(5) + (2-2)5 = 6(5) 30 + 0 = 30

-6y+3 = -7y+8 -6y+7y = 8-3 y = 5

10y= 6y+5+3y 10y=6+9y y=6

16

Subtracting gives: 10x = 80 so x = 8 and y = 5

X=7 y=5

-5/6

no it = 10

2x plus 6y equals 32 32 divided by 6= 5 R2 5+2= 7x6= 42-5=37-2=35 so X=5

-5x + 6y = 24 6y = 5x + 24 y = 5/6 x + 4 the slope is 5 6

6y - 5 = -5; so 6y = -5 + 5; so 6y = 0; so y = 0

People also asked